Theoretical and legal features of key institutions in Municipal Law - O. O. Kolobylina (Bulletin of Kharkiv National University of Internal Affairs)
It has been established that the institutions of Municipal Law are the key elements of the studied branch of law. This is due to the fact that they are more clear, specific and homogeneous regulatory elements with regard to their subject matter, which allows making certain structural and substantive changes to them without affecting other components of the Municipal Law system. The division into institutes helps to group legal norms that are homogeneous in terms of subject matter and methods of regulation, which contributes to a clearer definition of the main directions of the regulatory impact of Municipal Law and ensures more meaningful and efficient regulation of relevant legal relations, as well as the internal integrity and autonomy of the Municipal Law system.